Hydroxycitric acid content in local exotic fruits as a potential dietary supplement for weight reduction - Mohamed Zulkali, Mohamed Daud; Naimah, Ibrahim; Alina Rahayu, Mohamed; Ku Syahidah, Ku Ismail (Universiti Teknologi MARA (UiTM) & Institut Jurutera Kimia Malaysia (IJKM), 2011)
Link to publishers homepage at http://fkk.uitm.edu.my/